2016
DOI: 10.1093/nar/gkw1097
|View full text |Cite
|
Sign up to set email alerts
|

C3-symmetric opioid scaffolds are pH-responsive DNA condensation agents

Abstract: Herein we report the synthesis of tripodal C3-symmetric opioid scaffolds as high-affinity condensation agents of duplex DNA. Condensation was achieved on both supercoiled and canonical B-DNA structures and identified by agarose electrophoresis, viscosity, turbidity and atomic force microscopy (AFM) measurements. Structurally, the requirement of a tris-opioid scaffold for condensation is demonstrated as both di- (C2-symmetric) and mono-substituted (C1-symmetric) mesitylene-linked opioid derivatives poorly coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…While internalization of DNA/Ligand particles with diameters of between 50 and 100 nm is a relatively rapid process, particles up to 500 nm have shown good cell membrane transport, but an upper size limit of ≥1 μm is generally accepted . In contrast to previously reported MC3 (which has a similar molecular structure to HC3 ), AFM studies conducted with plasmid DNA (pUC19) identified large DNA aggregates ≥1 μM with visible free plasmid in the surrounding surface area . CC3 , on the other hand, produces tightly packed particles that may offer improved transfection efficacy and protection from endonuclease activity.…”
Section: Figurementioning
confidence: 86%
See 3 more Smart Citations
“…While internalization of DNA/Ligand particles with diameters of between 50 and 100 nm is a relatively rapid process, particles up to 500 nm have shown good cell membrane transport, but an upper size limit of ≥1 μm is generally accepted . In contrast to previously reported MC3 (which has a similar molecular structure to HC3 ), AFM studies conducted with plasmid DNA (pUC19) identified large DNA aggregates ≥1 μM with visible free plasmid in the surrounding surface area . CC3 , on the other hand, produces tightly packed particles that may offer improved transfection efficacy and protection from endonuclease activity.…”
Section: Figurementioning
confidence: 86%
“…This work focuses on the non‐analgesic use of opioids as a bio‐renewable resource capable of packaging DNA. While opioids are predominantly used for their potent analgesic properties, serving as one of the major drug classes within the pharmaceutical industry,, specific architectures were recently identified to have DNA binding properties . In that study, we identified morphine ( MC3 ), oripavine ( OC3 ) and heterocodeine ( HC3 ) C 3 ‐opioids could condense DNA.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in recent years, some efforts have also been contributed to develop C 3 ‐symmetric molecules in areas of catalysis and materials science, metal ions sensing, and biomolecular interaction and stabilization . However, examples found from the literature of designing C 3 ‐symmetric molecules for biological or biomolecular‐related investigations such as targeting amino acids and DNA are very rare. In the present study, we attempted to design a propeller‐like (C 3 ‐symmetric as shown in Scheme ) small organic molecule for the study of molecular interaction and fluorescent detection of human telomere G‐quadruplex DNA (telo21) under physiological conditions because telo21 DNA has the unique structural features that are able to contribute biological significance in telomere maintenance, transcription regulation and anti‐tumour chemotherapy …”
Section: Introductionmentioning
confidence: 99%